Optimizing Argumentative Writing in the Digital Era: The Impact of ProWritingAid to Student Confidence and the Difficulties of AI-Driven Editing - Sutrisno, Andy; Fitriati, Sri Wuli; Rozi, Fahrur (Institut Agama Islam Negeri Palopo, 2025)
This study examines the impact of ProWritingAid, an AI-driven writing tool, on improving writing accuracy and increasing confidence among vocational high school students studying English as a Foreign Language (EFL) in Indonesia. The study examines the difficulties vocational students encounter in creating coherent and grammatically precise argumentation writings, highlighting the necessity for efficient technology assistance in their writing advancement. A qualitative case study methodology was employed to gather data using semi-structured interviews, observations, and document analysis involving 21 eleventh-grade students at SMK Al-Washliyah Sukra. Thematic analysis utilizing NVivo software was conducted to discern major trends in students' motivation, confidence, and challenges encountered while using ProWritingAid. The results indicate that ProWritingAid markedly improves students' motivation and self-assurance by delivering prompt, constructive feedback on grammar, punctuation, and sentence structure, together with progress monitoring that cultivates a sense of accomplishment. Challenges include restricted access to premium capabilities, the intricacy of advanced ideas, internet connectivity problems, and device limits were recognized as impediments to optimal tool utilization. Notwithstanding these challenges, the tool significantly enhanced writing precision, assisting students in generating clearer and more logical arguing compositions. The study emphasizes the significance of including AI writing tools as supplementary resources in vocational education, while warning against excessive reliance and highlighting the necessity for instructional oversight. The study's limitations encompass its brief duration, cultural distinctiveness, and dependence on a singular version of the tool, potentially impacting generalizability. Subsequent study ought to investigate longitudinal impacts, cross-cultural relevance, and the incorporation of new AI technologies to enhance writing education in vocational EFL settings.